2015
DOI: 10.1002/j.1681-4835.2015.tb00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of Enterprise Architecture in the Namibian Government: The Use of Activity Theory to Examine the Influencing Factors

Abstract: Government in both developed and developing countries strive to deliver effective and efficient services to its citizens. Hence the rapid increasing use of information technology to enhance service delivery. However, IT carries its own challenges, such as incompatibilities, lack of integration and lack of scalability. Many approaches, from both academic and professional domains have been employed to assess the challenges, for improvement purposes. Government of some countries have therefore introduced enterpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…It was underscored that simply taking an IT perspective is a serious mistake [27], EAs were primarily product oriented while sociopolitical aspects were often neglected [29]. Non-technical factors were ignored or considered less significant than technical ones [30]. To address such non-technical issues, institutional aspects of applying EA in governments were investigated [28,31,32].…”
Section: Non-technical Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was underscored that simply taking an IT perspective is a serious mistake [27], EAs were primarily product oriented while sociopolitical aspects were often neglected [29]. Non-technical factors were ignored or considered less significant than technical ones [30]. To address such non-technical issues, institutional aspects of applying EA in governments were investigated [28,31,32].…”
Section: Non-technical Motivationmentioning
confidence: 99%
“…Similarly, it was reported that current EAs were primarily product oriented, with their sociopolitical aspects neglected often [29], and simply taking an IT perspective on EA as a prerequisite to e-government implementation was a serious mistake [27]. Both technical and nontechnical factors should be considered [30], and two key institutionalization techniques, inductive communication and deployment of experts to local contexts, might help overcome the struggles of translating new practices [32]. More concrete contributions were produced in some studies such as how EA was understood by public sector authorities [15], twenty challenges faced by the public sector agencies [17], sixteen problems and eight root causes in the context of public sectors [18] when developing and implementing EA.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness campaigns and training targeted at ordinary citizens educating them on the benefits of e‐government and providing content in local languages has been suggested to support effective use of technology (Bwalya, ; Mow, ; Ndou, ). Centres of excellence and training programs are proposed to uplift ICT skills in key disciplines (Nair & Prasad, ; Ndou, ; Shaanika & Iyamu, ; Tsokota et al, ). Napitupulu and Sensuse (), Mow (), and Tsokota et al () discuss the importance of regulatory assessments and monitoring for IT initiatives; factors which are not discussed in detail in the literature reviewed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, over 30 states within the United States of America have used the EA for their services (Bui, Markus & Newell, ). However, the development and implementation of the EA continue to be challenging in developing countries, particularly in the Africa continent (Shaanika & Iyamu, ). The challenges are attributed to non‐technical factors, which include environmental settings and cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%